The EU’s hospitality and welcome culture: conceiving the "no human being is illegal" principle in the EU fundamental freedoms and migration governance - Aliu, Armando (Human rights review, 2022)
This article aims to highlight the theoretical and philosophical debate on hospitality underlining the normative elements of framing migrants and refugees as individual agents in the light of hospitality theory and migration governance. It argued the critiques of the neo-Kantian hospitality approach and the EU welcome culture with regard to refugees in the EU from a philosophical perspective. The “No human being is illegal” motto is proposed to be conceived as a principle of the EU Charter of Fundamental Rights. The cosmopolitan right to visit and the universal right to reside were discussed in the context of human rights and co-responsibility. Linking the hospitality approach with migration governance enables the reconstruction of reception policies and practices, diversification of non-state actors that engage in migration governance mechanism, and polarization of political initiatives (e.g., politics of allocation and dispersal, readmission negotiations, convergence/divergence of priorities and strategic interests). The research findings highlight that the EU adopted a neo-Kantian hospitality approach that combines both “co-responsibility” and “vertical/heterarchical relations.” The EU’s “New Pact on Migration and Asylum” was considered proof of how the EU follows neo-Kantian hospitality that is manifested in dualism and contradictory approach. The study presents a typology that splits co-responsibility into individual/institutional actions and human rights/migration governance.